The Constitutional Court of Ukraine in the Mechanism for Ensuring the Right of Citizens of Ukraine to an Adequate Standard of Living - Kushnirenko, O. H. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the specificity of the activity of the Constitutional Court of Ukraine in the legal mechanism of ensuring the rights of citizens to an adequate standard of living is researched.